(untitled) (Zoological Archives: An International Journal, 2023)
Alpine ecosystems are among the most climate-sensitive environments on Earth: mountain habitats warm at approximately twice the global mean rate, snowpack timing and duration are shifting across all major mountain ranges, and the summit trap effect – where upward range shifts of cold-adapted species encounter diminishing habitat area at higher elevations – creates an extinction dynamic with no terrestrial analogue. The fauna of alpine zones above treeline encompass some of the most range-restricted and habitat-specialised vertebrate and invertebrate taxa globally, making them disproportionately vulnerable to climate-driven habitat loss even as they represent outstanding natural laboratories for evolutionary and ecological research. This study presents the first pan-European alpine fauna climate vulnerability assessment (CVA) covering 247 species from 18 alpine and subalpine zones across the Alps, Pyrenees, Scandinavian mountains, Carpathians, and Caucasus, applying a three-dimensional CVA framework quantifying exposure (projected climate change magnitude), sensitivity (species’ tolerance to climate change), and adaptive capacity (dispersal ability and evolutionary potential). Under the RCP 8.5 high-emissions scenario, 74.7% of assessed species showed high or very high overall vulnerability by 2080; under RCP 4.5, 47.4% remained high or very high. Summit-trap species (range-restricted to mountain tops with no higher-elevation habitat available) showed the highest vulnerability regardless of emissions scenario. Species distribution model projections indicated a mean 54.7% reduction in climatically suitable habitat area under RCP 8.5 by 2080, with 28.4% of species projected to lose > 80% of current suitable habitat.